1992
DOI: 10.1136/bmj.305.6846.152
|View full text |Cite
|
Sign up to set email alerts
|

Association between postpartum thyroid dysfunction and thyroid antibodies and depression.

Abstract: Patients who are functionally impaired are more likely to have emotional disorder, to believe in an infectious cause for their illness, to avoid alcohol, and to be members ofa patient selfhelp organisation. Prospective studies are required to determine the aetiological importance of these associations.We thank Penny Hagar and Susan Simkin for handling and scoring the questionnaires, and Oxfordshire Health Authority for financial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0
7

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(134 citation statements)
references
References 34 publications
5
108
0
7
Order By: Relevance
“…The results of Pop et al (1991), as well as the work of Harris et al (1992) and Pederson et al (1993), clearly demonstrate that thyroid dysfunction is associated with a small but signifi-cant fraction of PPD. 4 Nevertheless, in light of the strong associations of PPD with social support and infant variables, and its frequent occurrence in fathers, a strictly hormonal etiology for most cases of PPD is untenable.…”
Section: Tests Of the Defection Hypothesis For Postpartum Depressionmentioning
confidence: 90%
“…The results of Pop et al (1991), as well as the work of Harris et al (1992) and Pederson et al (1993), clearly demonstrate that thyroid dysfunction is associated with a small but signifi-cant fraction of PPD. 4 Nevertheless, in light of the strong associations of PPD with social support and infant variables, and its frequent occurrence in fathers, a strictly hormonal etiology for most cases of PPD is untenable.…”
Section: Tests Of the Defection Hypothesis For Postpartum Depressionmentioning
confidence: 90%
“…Fifty percent of pregnant women positive for thyroid peroxidase antibodies (TPOAb, identical to microsomal antibodies (MsAb)), will develop PPTD (3)(4)(5)(6). PPTD is clinically characterized by symptoms associated with hyper-and/or hypothyroidism and depressive symptoms (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Punzi et al (32) reported in patients with autoimmune thyroiditis and widespread joint pain that TPOAb level was positively correlated with the number of joints affected by pain, pain scores, and ESR levels. It was reported in another study that there was no association between TPOAb level and FM symptom scores, TgAb was positively correlated with ESR levels, and there was no significant difference in ESR levels of FM patients with or without autoimmunity (7).…”
Section: Discussionmentioning
confidence: 99%